Respostas

2014-04-21T15:55:09-03:00
Resolva as equações:
3x^2-5x-2=0
Δ = b² - 4 × a × c                               X = - b +- √Δ  /  2 × a
Δ = (- 5)² - 4 · 3 · (- 2)                         X = - (- 5) +- √49  /  2 · 3
Δ = 25 + 24                                       X = 5 +- 7  /  6              
Δ = 49                                                       
x' = 5 + 7  /  6 = 12  /  6 = 2           x" = 5 - 7  /  6 = - 2  /  6  = - 0,33
S = {2 , - 0,33}

5x-2=2x-1
5x - 2x = - 1 + 2
3x = 1
x =  \frac{1}{3} ou 0,33
S = {0,33}


Somando: - 0,33 + 0,33 = 0 + 2 = 2

Resposta: letra c

;)
5 4 5